2019
DOI: 10.1353/rhe.2019.0066
|View full text |Cite
|
Sign up to set email alerts
|

Effective Advising: How Academic Advising Influences Student Learning Outcomes in Different Institutional Contexts

Abstract: Using survey data from 156 bachelor's-granting institutions, this study explored the relationship between academic advising services and senior's grades and self-perceived gains. We found advising experiences has a positive relationship with students' grades and self-perceived learning gains. Additionally, our results indicate that the institutional advising climate is positively correlated with perceived learning gains, but not grades. The results also showed that the relationships of advising and students' l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The authors argued that the involvement theory explained how students' academic development was linked to the quantity and quality of academic advising received. Mu and Fosnacht (2016) also tested Astin's theory and found a positive link between academic advisory services and senior students' grades. The authors distributed a survey to 156 universities.…”
Section: Figure 2 Astin's Theory Of Student Involvementmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors argued that the involvement theory explained how students' academic development was linked to the quantity and quality of academic advising received. Mu and Fosnacht (2016) also tested Astin's theory and found a positive link between academic advisory services and senior students' grades. The authors distributed a survey to 156 universities.…”
Section: Figure 2 Astin's Theory Of Student Involvementmentioning
confidence: 97%
“…There are many theories that show evidence of the quality of advising, such as Astin's (1991) inputs-environment-outcomes (I-E-O) theory. A study by Mu and Fosnacht (2016) was guided by Astin theory (1991) and was carried out to explore the relationship between academic advising and students' outcomes. Mu and Fosnacht conducted the survey among 156 bachelor-granting colleges and universities and found a positive association between academic advising experiences and student GPA.…”
Section: The Quality Of Academic Advising In Higher Educationmentioning
confidence: 99%
“…Nonetheless, the authors did not investigate the use of Blackboard to manage and advise students in a proficient way within a specific and reasonable time. However, it is worth mentioning that some research has shown that the effectiveness of academic advising can influence the student outcome and hence plays a critical role in the educational process (Mu and Fosnacht, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…However, review of the literature indicated that very limited studies have been conducted to determine the students and academic advisors' perspective of academic advising's functions. While these are significant effects on the outcomes of academic advising [26], literature indicated that academic advising service in Malaysian public universities generally was rarely assessed, studied, and reported. Academic advising is one of the essential elements that supports students' success in higher education [25,27].…”
Section: Instrumentation For Assessing Student's and Academic Advisormentioning
confidence: 99%